Rekonstruksi laporan keuangan UMKM berbasis SAK EMKM untuk perencanaan keuangan: Studi kasus EDT Coffee - Priskila Anjeli Rondonuwu; Rudy J. Pusung; Steven J. Tangkuman (Manajemen Bisnis dan Keuangan Korporat, 2026)
Micro, small, and medium enterprises (MSMEs) contribute more than 60% of Indonesia's Gross Domestic Product, yet many, particularly coffee shops in the fast-growing culinary sector, still keep only rudimentary cash records without reference to any formal accounting standard such as the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) issued by the Indonesian Institute of Accountants. Prior studies on SAK EMKM implementation have mostly evaluated compliance levels descriptively, leaving a gap in quantitative evidence on how the omission of fixed-asset depreciation distorts reported profit and undermines financial planning decisions. This study aims to reconstruct and evaluate the implementation of SAK EMKM in preparing the financial statements of EDT Coffee, a coffee shop located in Winangun Atas, Pineleng, Minahasa, North Sulawesi, as a basis for financial planning decisions, using a single-case, descriptive qualitative case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of data reduction, data display, and conclusion drawing. The results show that EDT Coffee has not implemented SAK EMKM due to management's limited accounting knowledge, and its bookkeeping remains conventional, merely recording cash inflows and outflows. Its internal records were found to overstate profit by IDR 45,016,477 because non-cash depreciation expenses on fixed assets were disregarded. After reconstructing the Income Statement, Statement of Financial Position, and Notes to the Financial Statements in accordance with SAK EMKM, using the straight-line depreciation method with a 10% residual value, the entity's real net profit for fiscal year 2025 was found to be IDR 31,527,997. This reconstruction provides an accurate financial data foundation for the owner in formulating operational cost-efficiency strategies and long-term financial planning; as findings from a single case, however, they should be generalized to other coffee shops with caution.